A Novel Model of P‐Glycoprotein Inhibitor Screening Using Human Small Intestinal Organoids. Issue 3 (26th October 2016) - Zhao, Junfang; Zeng, Zhiyang; Sun, Jialiang; Zhang, Yuanjin; Li, Dali; Zhang, Xueli; Liu, Mingyao; Wang, Xin
Abstract: P‐glycoprotein (P‐gp), an important efflux transporter in intestine, regulates the bioavailability of orally taken drugs. To develop an in vitro model that preferably mimics the physiological microenvironment of human intestine, we employed the three‐dimensionally (3D) cultured organoids from human normal small intestinal epithelium. It was observed that the intestinal crypts could efficiently form cystic organoid structure with the extension of culture time. Furthermore, the physiological expression of ABCB1 was detected at both mRNA and protein levels in cultured organoids. Rhodamine 123 (Rh123), a typical substrate of P‐gp, was actively transported across 3D organoids and accumulated in the luminal space. This transport process was also inhibited by verapamil and mitotane. In summary, the above‐mentioned model based on human small intestinal 3D organoids is suitable to imitate the small intestinal epithelium and could be used as a novel in vitro model especially for P‐gp inhibitor screening.